1998
DOI: 10.1063/1.121909
|View full text |Cite
|
Sign up to set email alerts
|

Adatom diffusion at GaN (0001) and (0001̄) surfaces

Abstract: The diffusion of Ga and N adatoms has been studied for the technologically relevant wurtzite (0001) and (0001) surfaces employing density-functional theory. Our calculations reveal a very different diffusivity for Ga and N adatoms on the equilibrium surfaces: While Ga is very mobile at typical growth temperatures, the diffusion of N is by orders of magnitudes slower. These results give a very detailed insight of how and under which growth conditions N adatoms can be stabilized and efficiently incorporated at t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
310
1
7

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 460 publications
(345 citation statements)
references
References 16 publications
27
310
1
7
Order By: Relevance
“…In order to test this hypothesis, we have calculated diffusion pathways and migration energy barriers for Ga and N adatoms on the In-adlayer surface and compare these with prior calculations for bare GaN (0001) (i.e., in the absence of the In adlayer) [18]. For Ga adatoms on top of the In adlayer, we find qualitatively the same adsorption sites and diffusion pathway as on bare GaN (0001).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…In order to test this hypothesis, we have calculated diffusion pathways and migration energy barriers for Ga and N adatoms on the In-adlayer surface and compare these with prior calculations for bare GaN (0001) (i.e., in the absence of the In adlayer) [18]. For Ga adatoms on top of the In adlayer, we find qualitatively the same adsorption sites and diffusion pathway as on bare GaN (0001).…”
mentioning
confidence: 90%
“…We note that at high temperatures concerted interaction may modify this value. In contrast, diffusion of N adatoms on the bare surface occurs with a barrier of 1.3 eV [18]. An analysis of the PES for on-surface diffusion showed that diffusion barriers are significantly larger ( 1:5 eV) and that this PES is connected to the PES for AELD: For both PES the energetically most stable adatom configuration is the subsurface (H3) hollow site.…”
Section: P H Y S I C a L R E V I E W L E T T E R S Week Ending 7 Febrmentioning
confidence: 99%
“…The smoothing of the surface and the decrease of pit density are attributed to the Ga adatom surface diffusion. Since the surface adatom mobility is higher under Ga-rich conditions, faster adatom transport facilitates the filling of the surface pit defects and planarizes the morphology [13]. Once the coverage exceeds 2ML [ Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This approximation is expected to be well fulfilled, since previous theoretical and experimental studies showed that diffusion barriers on semiconductor surfaces are of the order of a few tenths of an eV up to a few eV. 8 Under these conditions transition state theory applies and the transition rate for an adatom jump from site i to iϩ1 is given by 9,10 …”
Section: Introductionmentioning
confidence: 99%